Adverse Childhood Experiences in Patients With Neurologic Disease. Issue 1 (February 2022) - Mendizabal, Adys; Nathan, Cody L.; Khankhanian, Pouya; Anto, Marissa; Clyburn, Cynthia; Acaba-Berrocal, Alexandra; Breen, Louise; Dahodwala, Nabila
Abstract : Background and Objectives: To describe the prevalence of high adverse childhood experiences (ACEs) among neurology outpatients and determine their association with health care utilization rates and comorbid medical and psychiatric disease. Methods: This was a cross-sectional study of adults seen for outpatient neurology follow-up at the University of Pennsylvania. Participants completed the ACE questionnaire and depression/anxiety screenings. Health care utilization metrics (emergency department [ED] visits, hospitalizations, and outpatient calls) were obtained for all participants. High ACE scores were defined as a score of ≥4. The prevalence of high ACE scores in our cohort was compared with US historical controls. Statistical associations were adjusted for age, sex, and race/ethnicity. Results: One hundred ninety-eight patients were enrolled in the study. Neurology patients were more likely to have elevated ACE scores compared with US population estimates (23.7% vs 12.6%, p < 0.01). High ACE scores were associated with increased ED utilization (odds ratio [OR] = 21, 95% CI [5.8–76.0], p < 0.01), hospitalizations (OR = 5.2, 95% CI [1.7–15.0], p < 0.01), and telephone encounters (OR 3, 95% CI [1.1–8.2], p < 0.05). High ACEs were also associated with medical and psychiatric comorbidities (OR 5.8, 95% CI [2.0–17.0], p < 0.01 and OR 4.5, 95% CI [2.1–9.6], p < 0.01) and high depression and anxiety scores (OR = 6.9, 95% CI [2.8–17.0], p < 0.01, and OR = 4.3, [95% CI 1.7–11.0], p < 0.01). Discussion: Patients with neurologic conditions are more likely to have high ACEs than the US population, which was associated with higher rates of health care utilization, increased number of medical and psychiatric comorbidities, and higher anxiety and depression scores. Addressing ACEs may be a way to improve the health outcomes of patients with neurologic conditions.